Question 1)
Given the function
f(x) = 2|x+10| - 6
You need to remember that:
f(x) = y
f(0) means we need to determine the value of y at x = 0.
so substitute x = 0 in the function
![f\left(x\right)\:=\:2|x+10|\:-\:6](https://img.qammunity.org/2022/formulas/mathematics/college/thxxpl2gm6ka6yivr8a2blct3uj86snuh7.png)
![f\left(0\right)\:=\:2|0+10|\:-\:6](https://img.qammunity.org/2022/formulas/mathematics/college/obe7sv9dyh8doqlhkwkb968yzp4tpr17zx.png)
![=2\left|10\right|-6](https://img.qammunity.org/2022/formulas/mathematics/college/ec0rnr1y87hlhgh7r3220706yndu3p3s71.png)
Apply absolute value:
![\left|a\right|=a,\:a\ge 0](https://img.qammunity.org/2022/formulas/mathematics/college/f792229odyfw9xgooznoeos0vrglpgyklg.png)
![=2\cdot \:10](https://img.qammunity.org/2022/formulas/mathematics/college/y9c7q2p7iakq6jbnhshgzj414g45zvc8lj.png)
![=20](https://img.qammunity.org/2022/formulas/mathematics/high-school/pj1rqrrg8jl4dzpxtrr6gj6sj9qij741k7.png)
Thus,
![f\left(0\right)\:=\:20](https://img.qammunity.org/2022/formulas/mathematics/college/1smsdcky4qnv37s41k9rouuxx93i0897nc.png)
Question 2)
Given the fuction
g(x) = x+1
substitute g(x) = 20 in the function
20 = x+1
x = 20-1
x = 19
Thus,
x = 0
Question 3)
Given the function
f(x)=2|x+10|-6
substitute x = 1 in the function
f(1)=2|1+10|-6
f(1)=2|1+10|-6
f(1) = 2|11| - 6
Apply absolute value:
![\left|a\right|=a,\:a\ge 0](https://img.qammunity.org/2022/formulas/mathematics/college/f792229odyfw9xgooznoeos0vrglpgyklg.png)
f(1) = 2(11) - 6
f(1) = 22 - 6
f(1) = 16
Given the function
g(x)=x+1
substitute x = 0 in the function
g(0) = 0+1
g(0) = 1
Thus,
g(0)+f(1) = 16+1
= 17